Compliance, mass distribution and contact forces in cursorial and scansorial locomotion with biorobotic physical models. (3rd April 2021) - Siddall, Robert; Fukushima, Toshihiko; Bardhi, Drilon; Perteshoni, Buna; Morina, Albulena; Hasimja, Era; Dujaka, Yll; Haziri, Gezim; Martin, Lina; Banerjee, Hritwick; Jusufi, Ardian
Abstract : Locomotion in unstructured and irregular environments is an enduring challenge in robotics. This is particularly true at the small scale, where relative obstacle size increases, often to the point that a robot is required to climb and transition both over obstacles and between locomotion modes. In this paper, we explore the efficacy of different design features, using 'morphological intelligence', for mobile robots operating in rugged terrain, focusing on the use of active and passive tails and changes in mass distribution, as well as elastic suspensions of mass. We develop an initial prototype whegged robot with a compliant neck and test its obstacle traversal performance in rapid locomotion with varying its mass distribution. Then we examine a second iteration of the prototype with a flexible tail to explore the effect of the tail and mass distribution in ascending a slope and traversing obstacles. Based on observations from these tests, we develop a new platform with increased performance and a fin ray wheel-leg design and present experiments on traversing large obstacles, which are larger than the robot's body, of this platform with tails of varying compliance. This biorobotic platform can assist with generating and testing hypotheses in robotics-inspired biomechanics of animal locomotion. GRAPHICAL ABSTRACT: